Circulating cell-free DNA in health and disease — the relationship to health behaviours, ageing phenotypes and metabolomics - Laura Kananen; Mikko Hurme; Alexander Bürkle; Maria Moreno-Villanueva; Jürgen Bernhardt; Florence Debacq-Chainiaux; Beatrix Grubeck-Loebenstein; Marco Malavolta; Andrea Basso; Francesco Piacenza; Sebastiano Collino; Efstathios S. Gonos; et al. (GeroScience, 2023)
Circulating cell-free DNA (cf-DNA) has emerged as a promising biomarker of ageing, tissue damage and cellular stress. However, less is known about health behaviours, ageing phenotypes and metabolic processes that lead to elevated cf-DNA levels. We sought to analyse the relationship of circulating cf-DNA level to age, sex, smoking, physical activity, vegetable consumption, ageing phenotypes (physical functioning, the number of diseases, frailty) and an extensive panel of biomarkers including blood and urine metabolites and inflammatory markers in three human cohorts (N = 5385; 17–82 years). The relationships were assessed using correlation statistics, and linear and penalised regressions (the Lasso), also stratified by sex. cf-DNA levels were significantly higher in men than in women, and especially in middle-aged men and women who smoke, and in older more frail individuals. Correlation statistics of biomarker data showed that cf-DNA level was higher with elevated inflammation (C-reactive protein, interleukin-6), and higher levels of homocysteine, and proportion of red blood cells and lower levels of ascorbic acid. Inflammation (C-reactive protein, glycoprotein acetylation), amino acids (isoleucine, leucine, tyrosine), and ketogenesis (3-hydroxybutyrate) were included in the cf-DNA level-related biomarker profiles in at least two of the cohorts. In conclusion, circulating cf-DNA level is different by sex, and related to health behaviour, health decline and metabolic processes common in health and disease. These results can inform future studies where epidemiological and biological pathways of cf-DNA are to be analysed in details, and for studies evaluating cf-DNA as a potential clinical marker.

Drug metabolizing enzyme expression in rat choroid plexus: effects of in vivo xenobiotics treatment - Daniela Gradinaru; Anne-Laure Minn; Yves Artur; Alain Minn; Jean-Marie Heydel (Archives of Toxicology, 2009)